Recent advances in the repair of degenerative intervertebral disc for preclinical applications - Ying, Yijian; Cai, Kaiwen; Cai, Xiongxiong; Zhang, Kai; Qiu, Rongzhang; Jiang, Guoqiang; Luo, Kefeng (Frontiers in Bioengineering and Biotechnology, 2023)
The intervertebral disc (IVD) is a load-bearing, avascular tissue that cushions pressure and increases flexibility in the spine. Under the influence of obesity, injury, and reduced nutrient supply, it develops pathological changes such as fibular annulus (AF) injury, disc herniation, and inflammation, eventually leading to intervertebral disc degeneration (IDD). Lower back pain (LBP) caused by IDD is a severe chronic disorder that severely affects patients' quality of life and has a substantial socioeconomic impact. Patients may consider surgical treatment after conservative treatment has failed. However, the broken AF cannot be repaired after surgery, and the incidence of re-protrusion and reoccurring pain is high, possibly leading to a degeneration of the adjacent vertebrae. Therefore, effective treatment strategies must be explored to repair and prevent IDD. This paper systematically reviews recent advances in repairing IVD, describes its advantages and shortcomings, and explores the future direction of repair technology.